Root systems of peanut cultivars respond differently to soil P availability to improve P uptake - Cordeiro, Carlos Felipe dos Santos [UNESP]; Echer, Fábio Rafael; Rosolem, Ciro Antonio [UNESP] (Wiley, 2024)
Background: Peanut (Arachis hypogaea L.) is regarded as a crop with high nutrient use efficiency, but there may be differences between cultivars. Furthermore, there is little information on the strategy of peanut cultivars to adapt to soil P availability and to what extent they explore non-labile P pools. Aims: Our objective was to evaluate growth, root morphology, enzymatic activity in the rhizosphere, and P uptake of peanut cultivars grown under different soil P status. Methods: The study was conducted in a greenhouse in 6-L pots. Soils with low P (without fertilization) and high P content (with fertilization) and seven peanut cultivars of different origins, different maturation groups, and release years were investigated. Peanut shoot yield, phosphorus uptake, root growth, soil P fractions as well as phosphatase activity in the rhizosphere soil were determined. Results: In P-deficient soil, a higher dry matter yield was associated with longer root hairs and root length, which resulted in decreased soil non-labile P was observed mainly with cultivars developed in Argentina (ARG-medium-old and ARG-medium-new) and the late maturity Brazilian cultivar (BR I-late new). These cultivars adapted well to P deficiency and were less dependent on labile P. New Brazilian early and medium maturity cultivars developed less, shorter root hairs, and showed low acid phosphatase activity in the rhizosphere under P deficiency, resulting in lower P uptake and dry matter yield. Under high P availability, new Brazilian cultivars of medium and late maturity showed the highest dry matter yield (9.0 and 9.8 g plant−1, respectively) and longest roots, around 120 m plant−1. High P availability decreased root hairs in all cultivars. Conclusion: Overall, the adaptation of peanut cultivars to P-deficient soils was lower for the new mid- and early-maturing Brazilian cultivars compared with the Argentinian and old or late-maturing Brazilian cultivars. The main strategies of P-efficient cultivars under low P availability are to increase root length, root hair length, and root hair density.
Keywords: acid phosphatase activity; phosphorus availability; phosphorus uptake; root hair density; root hair length; root length